2002
DOI: 10.1074/jbc.m201198200
|View full text |Cite
|
Sign up to set email alerts
|

Presteady-state Analysis of a Single Catalytic Turnover by Escherichia coli Uracil-DNA Glycosylase Reveals a “Pinch-Pull-Push” Mechanism

Abstract: Uracil-DNA glycosylase catalyzes the excision of uracils from DNA via a mechanism where the uracil is extrahelically flipped out of the DNA helix into the enzyme active site. A conserved leucine is inserted into the DNA duplex space vacated by the uracil leading to the paradigmatic "push-pull" mechanism of nucleotide flipping. However, the order of these two steps during catalysis has not been conclusively established. We report a complete kinetic analysis of a single catalytic turnover using a hydrolyzable du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
69
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 47 publications
(49 reference statements)
5
69
0
Order By: Relevance
“…When analysing kinetic parameters of E. coli Ung L191A against single-stranded substrates, a 15-fold reduction in k cat /K m was observed compared to the wild type (Handa et al, 2001;Jiang and Stivers, 2001), which would not be expected in the absence of stabilizing base pairing. A likely explanation for this could be that the leucine side chain rather functions as a 'doorstop' to prevent return of the flipped out uracil residue, as recently suggested by Wong et al (2002). Using stopped-flow experiments of E. coli Ung and monitoring fluorescence of 2-aminopurine adjacent to uracil, they demonstrated that Leu191 insertion occurred after nucleotide-flipping but before excision, thus indicating a 'pinch -pull -push' rather than a 'pinch -push -pull' mechanism.…”
Section: The Catalytic Domain Of Ung Proteinsmentioning
confidence: 99%
“…When analysing kinetic parameters of E. coli Ung L191A against single-stranded substrates, a 15-fold reduction in k cat /K m was observed compared to the wild type (Handa et al, 2001;Jiang and Stivers, 2001), which would not be expected in the absence of stabilizing base pairing. A likely explanation for this could be that the leucine side chain rather functions as a 'doorstop' to prevent return of the flipped out uracil residue, as recently suggested by Wong et al (2002). Using stopped-flow experiments of E. coli Ung and monitoring fluorescence of 2-aminopurine adjacent to uracil, they demonstrated that Leu191 insertion occurred after nucleotide-flipping but before excision, thus indicating a 'pinch -pull -push' rather than a 'pinch -push -pull' mechanism.…”
Section: The Catalytic Domain Of Ung Proteinsmentioning
confidence: 99%
“…First, the structural information on cognate and nonspecific complexes suggests that loop positioning is determined by the sequence of the bound DNA, thus providing a molecular basis for an inducedfit mechanism. Second, the temporal assignment of loop movement in relation to other known steps in the reaction cycle, such as base flipping, could be insightful for understanding if these processes are enzyme-assisted or occur passively (9,34). Third, our recent work on M.HhaI and other DNA methyltransferases suggests that conformational rearrangements such as the loop movement in M.HhaI or DNA bending by M.EcoRI can directly contribute to specificity (29,30,35).…”
mentioning
confidence: 99%
“…The amplitude of the burst phase, therefore, provided a direct measure of the molar amount of productively bound substrate during the initial turnover (45)(46)(47). In active site titrations, burst amplitudes were measure at different MutY and DNA concentrations.…”
mentioning
confidence: 99%